Agroecology and Integrated Rice– Fish Systems: Pathways to Food and Nutritional Security in Eastern India - Samaddar, Ayan; Singh, Sonali; Malaiappan, Sudharsan; Majumder, Rajib; Shenoy, Neetha; Teoh, Shwu Jiau; Panemangalore, Arun; Freed, Sarah; saha, subrata (WorldFish, 2025)
Integrated Rice Fish Systems (IRFS) offer a viable substitute for rice monoculture. They efficiently use the rice field ecosystem’s inherent productivity and available resources to provide the farming community with better economic and nutritional gains. IRFS adoption remains poor in Eastern India, despite favorable geographic conditions, natural resource availability, traditional knowledge, necessity for economic growth, and preference of rural communities for a rice and fish-based diet. To investigate whether agroecology (AE) could accelerate an IRFS-based transition towards food and nutritional security (FNS), this review of 194 scientific articles on IRFS from 2004 to 2024 documented the AE traits of IRFS and their relevance to addressing FNS. The current IRFS of Eastern India were assessed, first through a rapid review process to identify their qualitative traits consistent with AE. Next, we evaluated IRFS’ impact on FNS. In total, IRFS has shown 52 traits relevant to AE principles and that address FNS. Among 13 AE principles, seven have been considered primary impact creators of FNS. Impact may be accelerated with strategies such as crop diversification, mixed crop-livestock systems, and farmer-to-farmer networks. Fish play a significant role in IRFS by preserving ecological and socioeconomic equilibrium, supporting livelihoods, income, and community engagement. In Eastern India, an analysis of five distinct IRFS types identified qualitative features that could support a maximum of 10 relevant AE principles, but for which pertinent empirical evidence was lacking. Although IRFS could potentially boost smallholder income, FNS, and overall productivity, Eastern India would need to address seven significant challenges, including initial investment costs, vulnerability to natural disasters, hilly terrain, loss of indigenous fish varieties, environmental impacts of inputs, land-use change, limited technical knowledge and financial constrains among the farming communities. AE frameworks can support scaling up IRFS adoption and diffusion through a holistic approach to performance evaluation and creating appropriate strategies and guidelines.